2002
DOI: 10.1002/humu.9085
|View full text |Cite
|
Sign up to set email alerts
|

KCNQ1 and KCNH2 mutations associated with long QT syndrome in a Chinese population

Abstract: The long QT syndrome (LQTS) is a cardiac disorder characterized by prolongation of the QT interval on electrocardiograms (ECGs), syncope and sudden death caused by a specific ventricular tachyarrhythmia known as torsade de pointes. LQTS is caused by mutations in ion channel genes including the cardiac sodium channel gene SCN5A, and potassium channel subunit genes KCNQ1, KCNH2, KCNE1, and KCNE2. Little information is available about LQTS mutations in the Chinese population. In this study, we characterized 42 Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 11 publications
0
18
0
1
Order By: Relevance
“…Therefore, it is possible that there are other genes that regulate the QTc interval. Most previous studies focused on candidate regulation genes (Busjahn et al, 1999;Liu et al, 2002) already known as LQTS genes, but in order to identify unknown genes that regulate the QTc interval in the general population, a population-based whole genome study is necessary. An isolated population is appropriate for identifying genes that are responsible for complex traits because such a population reduces genetic heterogeneity and environmental diversity.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is possible that there are other genes that regulate the QTc interval. Most previous studies focused on candidate regulation genes (Busjahn et al, 1999;Liu et al, 2002) already known as LQTS genes, but in order to identify unknown genes that regulate the QTc interval in the general population, a population-based whole genome study is necessary. An isolated population is appropriate for identifying genes that are responsible for complex traits because such a population reduces genetic heterogeneity and environmental diversity.…”
Section: Introductionmentioning
confidence: 99%
“…In order to better understand the genetic characteristics of Chinese type 1 long QT syndrome pedigrees, we reviewed all related published studies regarding genotype-phenotype correlations. [21][22][23][24][25][26][27][28][29] The corrected QT interval of all type 1 long QT syndrome probands ranged from 490 to 680 ms (568 ± 13 ms, n = 18). The longest corrected QT of 680 ms was reported in one proband with mutation S277L located in the S5 region of the Kv7.1 channel.…”
Section: Discussionmentioning
confidence: 99%
“…Of these C-terminal mutations, three probands suffered from recurrent syncope and two probands' family members had a history of syncope, consistent with our findings. Although some of those nine Chinese studies (e.g., Liu et al 22 ) revealed a family history of sudden cardiac death, none of them presented any proband with C-terminal mutation suffering sudden cardiac death finally, or with P-loop domain mutation who benefited from metoprolol. Our study, therefore, further filled a gap in the gene mutations database regarding Chinese type 1 long QT syndrome patients and might be of great benefit for the early prevention and development of individual therapeutics.…”
Section: Discussionmentioning
confidence: 99%
“…In the previous studies, we firstly reported the LQTS mutation in the Chinese population and others continued to report on it [14,15]. But, the study of LQTS mutation function is the next step.…”
Section: Introductionmentioning
confidence: 96%